GLP-1 reduces metalloproteinase-9 induced by both hyperglycemia and hypoglycemia in type 1 diabetes. The possible role of oxidative stress - Ceriello A; La Sala L; De Nigris V; Pujadas G; Rondinelli M; Genovese S (Dove Medical Press, 2015)
Antonio Ceriello,1,2 Lucia La Sala,1 Valeria De Nigris,1 Gemma Pujadas,1 Maurizio Rondinelli,3 Stefano Genovese3 1Institut d’Investigación Biomédiques August Pi i Sunyer (IDIBAPS), 2Centro de Investigación Biomedica en Red de Diabetes y Enfermedades Metabolicas Asociadas (CIBERDEM), Hospital Clinic, Barcelona, Spain; 3Department of Cardiovascular and Metabolic Diseases, IRCCS Gruppo Multimedica, Sesto San Giovanni (MI), ItalyDear editorMMP-9 has been involved in favoring cardiovascular disease, and evidence suggests that oxidative stress favors its release. Previous studies demonstrated that during both acute hyperglycemia and hypoglycemia an oxidative stress is produced in type 1 diabetes. On the other hand, GLP-1 has shown an antioxidant power. In this study an acute hyperglycemia and hypoglycemia, with or without the simultaneous infusion of GLP-1, were produced. During both hyperglycemia and hypoglycemia, an acute increase of MMP-9 and 8-iso-PGF2α plasma levels was observed. GLP-1 significantly reduced this increase. This study suggests that metalloproteinase-9 is activated by acute hyperglycemia and hypoglycemia because they generate an oxidative stress and that GLP-1 counteracts this effect.